Compliment Strategies Employed by Japanese and Malaysian Tour Guides during Tour Sessions - Roswati, Abdul Rashid; Roslina, Mamat; Rokiah, Paee (The Global Council for Anthropological Linguistics, 2020)
This research is a comparative study of Japanese language communication between the Japanese and Malay tourist guides during the visit of tourism tour sessions. The research goal is to examine patterns of compliment strategies implemented throughout the interaction of the tour sessions. The study results acquired are in the forms of four recordings of a dialogue between the tourist guides and the tourists in audio and video modes. The conversations are transcribed and coded. Tourist guides included two Japanese native speakers and two Malaysian-Japanese speakers. In contrast, the tourists included are Japanese native speakers who came to visit Malaysia and Malaysians, who attended the tourist attractions in Japan. The conclusions of the study reveal that the frequency of compliment applied by both Japanese and Malaysian tour guides are alike, or in other words, there are no significant differences. Nevertheless, category, function and topic or theme of compliment utterance presents substantial distinctions. I am looking forward that this investigation could be adopted as a reference for those who study the Japanese language for tourism and to develop cross-cultural communication proficiency.